Odpowiedzi

2010-03-02T21:24:33+01:00
A) 3x-y+x-1=4x-y-1
b) 3x-y+x-1-(-3x-y)= 4x-y-1+3x+y= 7x-1
c)3x-y-(x-1)-(-3x-y)= 3x-y-x+1+3x+y= 5x+1
d) 3x-y-[x-1-(-3x-y)]= 3x-y-[x-1+3x+y]= 3x-y-4x+1-y= -x-2y+1
3 3 3
2010-03-02T21:27:46+01:00
A) 3x-y+x-1
4x-y-1

b) 3x-y+x-1-(-3x-y)
3x-y+x-1+3x+y
7x-1

c) 3x-y-x-1-(-3x-y)
3x-y-x-1+3x+y
5x-1

d) 3x-y-[x-1-(-3x-y)]
3x-y-(x-1+3x+y)
3x-y-x+1-3x-y
-x-2y+1
4 4 4
2010-03-02T21:28:50+01:00
ODPOWIEDŻ
a.)
3x-y+x-1=4x-y-1
b)
3x-y+x-1-(-3x-y) = 3x-y+x-1+3x+y = 7x-1
c)
3x-y-x-1-(-3x-y) = 3x-y-x-1+3x+y = 5x-1
d)
3x-y-(x-1-3x-y) = 3x-y-x+1+y = 5x+1
3 3 3